LncRNA JHDM1D-AS1 Is a Key Biomarker for Progression and Modulation of Gemcitabine Sensitivity in Bladder Cancer Cells - Pereira, Isadora Oliveira Ansaloni; da Silva, Glenda Nicioli; Almeida, Tamires Cunha; Lima, Ana Paula Braga; Sávio, André Luiz Ventura; Leite, Katia Ramos Moreira; Salvadori, Daisy Maria Fávero [UNESP] (MDPI, 2023)
Long non-coding RNAs are frequently found to be dysregulated and are linked to carcinogenesis, aggressiveness, and chemoresistance in a variety of tumors. As expression levels of the JHDM1D gene and lncRNA JHDM1D-AS1 are altered in bladder tumors, we sought to use their combined expression to distinguish between low-and high-grade bladder tumors by RTq-PCR. In addition, we evaluated the functional role of JHDM1D-AS1 and its association with the modulation of gemcitabine sensitivity in high-grade bladder-tumor cells. J82 and UM-UC-3 cells were treated with siRNA-JHDM1D-AS1 and/or three concentrations of gemcitabine (0.39, 0.78, and 1.56 µM), and then submitted to cytotoxicity testing (XTT), clonogenic survival, cell cycle progression, cell morphology, and cell migration assays. When JHDM1D and JHDM1D-AS1 expression levels were used in combination, our findings indicated favorable prognostic value. Furthermore, the combined treatment resulted in greater cytotoxicity, a decrease in clone formation, G0/G1 cell cycle arrest, morphological alterations, and a reduction in cell migration capacity in both lineages compared to the treatments alone. Thus, silencing of JHDM1D-AS1 reduced the growth and proliferation of high-grade bladder-tumor cells and increased their sensitivity to gemcitabine treatment. In addition, the expression of JHDM1D/JHDM1D-AS1 indicated potential prognostic value in the progression of bladder tumors.
Keywords: bladder cancer; JHDM1D-AS1; long non-coding RNAs